COMMUNITY DIVERSITY AND RELIGIOU COMMUNITY DIVERSITY AND RELIGIOUS TOLERANCE IN THE HISTORY OF THE KINGDOM OF SRIWIJAYA - Agustina, Renita Agustina (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2020)
The Sriwijaya Kingdom in its golden age was visited by many foreign traders (Arab, Indian Chinese) who came to Sriwijaya for trade and other interests, so that it would indirectly affect the diversity of society as well as lead to a tolerant life in Sriwijaya. The purpose of this study is to analyze the diversity of people in Sriwijaya in various aspects of life, tolerance between religious communities such as Buddhism, Islam and Hinduism, and the factors that emerge in the life of tolerance in Sriwijaya. The method used is the historical method or historical method. The steps in the historical method include heuristics (data collection / sources), verification (selection or source criticism), interpretation (historical interpretation) and finally historiography (writing history). This research explains the condition of the diversity of the Sriwijaya community, starting from the indigenous people, Arabs, Indians and Chinese, these foreigners are in Sriwijaya because of the economic factors they enter into trading. The diversity of people in Sriwijaya was very much protected by the king of Sriwijaya, there was no emphasis, The Sriwijaya Kingdom in its golden age was visited by many foreign traders (Arab, Indian Chinese) who came to Sriwijaya for trade and other interests, so that it would indirectly affect the diversity of society as well as lead to a tolerant life in Sriwijaya. The purpose of this study is to analyze the diversity of people in Sriwijaya in various aspects of life, tolerance between religious communities such as Buddhism, Islam and Hinduism, and the factors that emerge in the life of tolerance in Sriwijaya. The method used is the historical method or historical method. The steps in the historical method include heuristics (data collection / sources), verification (selection or source criticism), interpretation (historical interpretation) and finally historiography (writing history). This research explains the condition of the diversity of the Sriwijaya community, starting from the indigenous people, Arabs, Indians and Chinese, these foreigners are in Sriwijaya because of the economic factors they enter into trading. The diversity of people in Sriwijaya was very much protected by the king of Sriwijaya, there was no emphasis,